2020
DOI: 10.1128/msphere.00807-19
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of Bat Coronaviruses through Surveillance and Probe Capture-Based Next-Generation Sequencing

Abstract: Coronaviruses (CoVs) of bat origin have caused two pandemics in this century. Severe acute respiratory syndrome (SARS)-CoV and Middle East respiratory syndrome (MERS)-CoV both originated from bats, and it is highly likely that bat coronaviruses will cause future outbreaks. Active surveillance is both urgent and essential to predict and mitigate the emergence of these viruses in humans. Next-generation sequencing (NGS) is currently the preferred methodology for virus discovery to ensure unbiased sequencing of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 24 publications
0
89
0
1
Order By: Relevance
“…It is also reported that Spike glycoprotein of the Wuhan coronavirus is modified via homologous recombination. The spike glycoprotein of SARS-CoV-2 is the mixture of bat SARS-CoV and a not known Beta-CoV (38). In a fluorescent study, it was confirmed that the SARS-CoV-2 also uses the same ACE2 (angiotensin-converting enzyme 2) cell receptor and mechanism for the entry to host cell which is previously used by the SARS-CoV (39,40).…”
Section: Genomic Variations In Sars-cov-2mentioning
confidence: 85%
“…It is also reported that Spike glycoprotein of the Wuhan coronavirus is modified via homologous recombination. The spike glycoprotein of SARS-CoV-2 is the mixture of bat SARS-CoV and a not known Beta-CoV (38). In a fluorescent study, it was confirmed that the SARS-CoV-2 also uses the same ACE2 (angiotensin-converting enzyme 2) cell receptor and mechanism for the entry to host cell which is previously used by the SARS-CoV (39,40).…”
Section: Genomic Variations In Sars-cov-2mentioning
confidence: 85%
“…Investigations suggest that the spike glycoprotein of SARS-CoV-2 is the result of the combination of a bat SARS-CoV with an unknown Beta-CoV [13], probably a coronavirus of pangolin origin. The S1 subunit containing the receptor-binding domain region of the spike protein of Pangolin-CoV is much more closely related to that of SARS-CoV-2 than to that of the bat coronavirus RaTG13.…”
Section: Inflammation Researchmentioning
confidence: 99%
“…However, so far, there is no evidence that the seafood market is the original source of SARS-CoV-2 (Guo et al, 2020). Before SARS-CoV-2, 4 types of beta coronaviruses can infect humans, including SARS-CoV and MERS-CoV which are highly pathogenic and both originated from bats (Li et al, 2020a; Liu et al, 2020b). Genome analysis showed that SARS-CoV-2 has 96.2% overall genome sequence identity with Bat CoV RaTG13, indicating that SARS-CoV-2 could also originate from bats (Zhou et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%